EFFECTS OF THE CURING TEMPERATURE ON GLASS FIBRE REINFORCED BASIC MAGNESIUM SULFATE CEMENT - Panpan Liu; Chengyou Wu; Luo Kejie; Chen Cong; Chen Yuanji; Zhang Huifang; Yu Hongfa (Ceramics-Silikáty, 2019)

(untitled)
In order to investigate the effect of different curing conditions on the properties of glass fibre reinforced basic magnesium sulfate cement (GRBMS), the compressive strength, flexural strength, and water resistance of the GRBMS were determined for five curing modes at 20 °C, 50 °C, and 80 °C. The phase composition of the hydrated product was analysed by X-ray diffraction and the microstructure was analysed using scanning electron microscopy (SEM) images. The results show that the curing temperature in the early stage of curing has a significant effect on the type of the primary reaction products. The main strength phase, resulting from the curing temperatures of 20 °C and 50 °C, is the 517 needle-like phase, whereas the curing temperature of 80 °C produces the 513 sheet-like phase. The strength phase of the cement-based material is the 517 phase when cured at 20 °C for 1 day; after curing at 80 °C for 3 days, the 517 phase loses water and changes into the 513 phase, changing the morphology. The pre-curing specimens have the lowest water resistance at 80 °C, indicating that the water resistance of the GRBMS sample is affected by both the curing temperature and the curing mode.